Estimating Efficiency Levels of County Health Facilities in Kenya Pre and During COVID 19 Period using DEA Methodology - Lutta, Paul; Munialo, Sussy; Muhonja, Faith Hope (African Economic Research Consortium, 2024)
Provision of quality, effective and efficient health service delivery remains a major concern for many governments all over the world. To achieve this requires efficient utilization of health resources to achieve improved health outcomes. In Kenya, health is one of the devolved functions managed by the county governments. Since inception of devolution, huge amount of public resources have been spent in provision of health services
Article
Keywords: health service delivery